Fuzzy Logic Implementation in Determining Sponge Cake Characteristics Based on Temperature and Baking Time - Farel Rizandi; Daffa Zulqisthi; Mrr. Lukie Trianawati; Farhan Ghibthi Fathon; Vina Fitri Ramadani; Syifa Nasywa Handayani; Salma Adiibah Putri; Nahda Adrianeu Putri; Giannisa Nabilla; Dipta Larasati; Muhammad Faiz Assariy (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Cake is a popular sweet food made primarily from wheat flour, sugar, eggs, and milk processed by baking. Sponge cake is one of the most popular types of cake. Sponge cake has a slightly rough texture and has large pores like sponge. Baking temperature and time have a crucial role in achieving optimal volume, texture, and density of the sponge cake. Overbaking and underbaking can negatively impact the moisture and softness. The purpose of this research is to determine the optimal temperature and baking time to produce a good sponge cake. The methods used in this research include a literature review and the implementation of fuzzy logic coupled with MATLAB application toolbox. The results of this research must be present a solution to optimize temperature control and baking time that can help produce consistent and high quality sponge cake products. However, the results are uncomprehensive.